Past Warmth and Its Impacts During the Holocene Thermal Maximum in Greenland - Axford, Yarrow; De Vernal, Anne; Osterberg, Erich C. (Annual Review of Earth and Planetary Sciences, 2021)
Higher boreal summer insolation in the early to middle Holocene drove thousands of years of summer warming across the Arctic. Modern-day warming has distinctly different causes, but geologic data from this past warm period hold lessons for the future. We compile Holocene temperature reconstructions from ice, lake, and marine cores around Greenland, where summer temperatures are globally important due to their influence on ice sheet mass balance, ocean circulation, and sea ice. Highlighting and accounting for some key issues with proxy interpretation, we find that much of Greenland experienced summers 3 to 5°C warmer than the mid-twentieth century in the early Holocene—earlier and stronger warming than often presumed. Warmth had dramatic consequences: Many glaciers disappeared, perennial sea ice retreated, plants and animals migrated northward, the Greenland Ice Sheet shrank rapidly, and increased meltwater discharge led to strong marine water stratification and enhanced winter sea ice in some areas. ▪ Summer air temperatures and open ocean temperatures around much of Greenland peaked in the early Holocene in response to elevated summer insolation. ▪ Peak summer air temperatures ranged from 3 to 5°C warmer than the mid-twentieth century in northwest and central Greenland to perhaps 1 to 2°C warmer in south Greenland. ▪ Many differences between records can be explained by proxy seasonality, ice sheet elevation changes, vegetation analogs and lags, and the nearshore effects of ice sheet meltwater. ▪ Early Holocene warmth dramatically affected glaciers and the Greenland Ice Sheet; meltwater discharge, nearshore ocean salinity, and sea ice; and diverse flora and fauna.

Large-scale features of Last Interglacial climate: results from evaluating the lig127k simulations for the Coupled Model Intercomparison Project (CMIP6)–Paleoclimate Modeling Intercomparison Project (PMIP4) - Otto-Bliesner, Bette L.; Brady, Esther C.; Zhao, Anni; Brierley, Chris M.; Axford, Yarrow; Capron, Emilie; Govin, Aline; Hoffman, Jeremy S.; Isaacs, Elizabeth; Kageyama, Masa; Scussolini, Paolo; Tzedakis, Polychronis C.; et al. (Climate of the Past, 2021)
Abstract. The modeling of paleoclimate, using physically based tools, is increasingly seen as a strong out-of-sample test of the models that are used for the projection of future climate changes. New to the Coupled Model Intercomparison Project (CMIP6) is the Tier 1 Last Interglacial experiment for 127 000 years ago (lig127k), designed to address the climate responses to stronger orbital forcing than the midHolocene experiment, using the same state-of-the-art models as for the future and following a common experimental protocol. Here we present a first analysis of a multi-model ensemble of 17 climate models, all of which have completed the CMIP6 DECK (Diagnostic, Evaluation and Characterization of Klima) experiments. The equilibrium climate sensitivity (ECS) of these models varies from 1.8 to 5.6 ∘C. The seasonal character of the insolation anomalies results in strong summer warming over the Northern Hemisphere continents in the lig127k ensemble as compared to the CMIP6 piControl and much-reduced minimum sea ice in the Arctic. The multi-model results indicate enhanced summer monsoonal precipitation in the Northern Hemisphere and reductions in the Southern Hemisphere. These responses are greater in the lig127k than the CMIP6 midHolocene simulations as expected from the larger insolation anomalies at 127 than 6 ka. New synthesis for surface temperature and precipitation, targeted for 127 ka, have been developed for comparison to the multi-model ensemble. The lig127k model ensemble and data reconstructions are in good agreement for summer temperature anomalies over Canada, Scandinavia, and the North Atlantic and for precipitation over the Northern Hemisphere continents. The model–data comparisons and mismatches point to further study of the sensitivity of the simulations to uncertainties in the boundary conditions and of the uncertainties and sparse coverage in current proxy reconstructions. The CMIP6–Paleoclimate Modeling Intercomparison Project (PMIP4) lig127k simulations, in combination with the proxy record, improve our confidence in future projections of monsoons, surface temperature, and Arctic sea ice, thus providing a key target for model evaluation and optimization.

A global database of Holocene paleotemperature records - Kaufman, Darrell; McKay, Nicholas; Routson, Cody; Erb, Michael; Davis, Basil; Heiri, Oliver; Jaccard, Samuel; Tierney, Jessica; Dätwyler, Christoph; Axford, Yarrow; Brussel, Thomas; Cartapanis, Olivier; et al. (Scientific Data, 2020)
Abstract A comprehensive database of paleoclimate records is needed to place recent warming into the longer-term context of natural climate variability. We present a global compilation of quality-controlled, published, temperature-sensitive proxy records extending back 12,000 years through the Holocene. Data were compiled from 679 sites where time series cover at least 4000 years, are resolved at sub-millennial scale (median spacing of 400 years or finer) and have at least one age control point every 3000 years, with cut-off values slackened in data-sparse regions. The data derive from lake sediment (51%), marine sediment (31%), peat (11%), glacier ice (3%), and other natural archives. The database contains 1319 records, including 157 from the Southern Hemisphere. The multi-proxy database comprises paleotemperature time series based on ecological assemblages, as well as biophysical and geochemical indicators that reflect mean annual or seasonal temperatures, as encoded in the database. This database can be used to reconstruct the spatiotemporal evolution of Holocene temperature at global to regional scales, and is publicly available in Linked Paleo Data (LiPD) format.